2021
DOI: 10.2460/javma.258.6.648
|View full text |Cite
|
Sign up to set email alerts
|

Association between antimicrobial treatment of subclinical pneumonia in foals and selection of macrolide- and rifampicin-resistant Rhodococcus equi strains at horse-breeding farms in central Kentucky

Abstract: OBJECTIVE To compare soil concentrations of macrolide- and rifampicin-resistant Rhodococcus equi strains (MRRE) on horse-breeding farms that used thoracic ultrasonographic screening (TUS) to identify foals with subclinical pneumonia combined with subsequent administration of macrolides and rifampin to affected foals (TUS farms) versus soil concentrations on farms that did not (non-TUS farms), determine whether the combined use of TUS and antimicrobial treatment of subclinically affected foals was associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…The mortality of AIDS patients with combined R. equi infection was as high as 20%~58% ( Ahumada et al., 2020 ). With the extensive application of antibiotics, reports of multidrug-resistance in R. equi are increasing, including resistance to trimethoprim, sulfamethoxazole, ampicillin sulbactam, clindamycin, erythromycin and rifampicin ( Petry et al., 2020 ; Alvarez-Narvaez et al., 2021a ; Huber et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mortality of AIDS patients with combined R. equi infection was as high as 20%~58% ( Ahumada et al., 2020 ). With the extensive application of antibiotics, reports of multidrug-resistance in R. equi are increasing, including resistance to trimethoprim, sulfamethoxazole, ampicillin sulbactam, clindamycin, erythromycin and rifampicin ( Petry et al., 2020 ; Alvarez-Narvaez et al., 2021a ; Huber et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In that study, the number of foals treated with macrolides and rifampin was significantly associated with the prevalence of MDR‐ R. equi in the environment 27 . Subsequently, the use of thoracic ultrasonography was associated both with greater use of antimicrobials to treat subclinical R. equi pneumonia among and with greater environmental concentrations of MDR‐ R. equi at horse‐breeding farms 26 . Genetic sequencing of 144 isolates collected from the soil of 100 horse‐breeding farms in the previously cited study 27 identified MDR‐ R. equi carrying both the known pRErm46 plasmid and a novel MLS B resistance gene, erm (51) 49 .…”
Section: Epidemiologymentioning
confidence: 86%
“…R. equi invades and replicates within macrophages due to the presence of virulence‐associated protein A (VapA), a surface‐expressed protein necessary to cause disease in foals 21 . Infection with R. equi occurs by inhalation of aerosolised virulent R. equi which are widely distributed in the environment at horse‐breeding farms 10,16,22–28 . Factors contributing to the aerosolisation of R. equi , such as a dry climate and density of mares and foals in paddocks, are associated with higher airborne concentration of R. equi and to higher infection rates 10 .…”
Section: Epidemiologymentioning
confidence: 99%
“…An accurate minimally invasive test for diagnosis of foals presumed to have pneumonia caused by R. equi would be useful for equine veterinary medicine because TBAs are not routinely performed by veterinarians at farms where R. equi is endemic and because overuse of antimicrobials to treat foals with subclinical pneumonia has contributed to the emergence of an alarming level of antimicrobial resistance in R. equi isolated from foals and their environment in the United States. [10][11][12][13][14][15][16][17] For this reason, we investigated the ability of qPCR of fecal swabs (which can be collected conveniently from foals) to differentiate between cases of pneumonia attributed to R. equi and healthy controls at 2 horse breeding farms in New York. Fecal concentrations of vapA from rectal swab samples were significantly greater in samples from foals with pneumonia attributed to R. equi than agematched controls and the typical magnitude of difference was nearly 100-fold (Figure 2).…”
Section: Discussionmentioning
confidence: 99%